Cerebral Ischemia after Stenting of Coarctation of the Aorta - D. Doughmi; S. Benlamkaddem; M. A. Berdai; S. Atmani; M. Harandou (International Journal of Pediatrics)
Percutaneous stenting angioplasty of native coarctation of the aorta is considered a low-risk procedure with high success rate. The incidence of cerebral complications, especially ischemic complications, is very low. We report a case of a 15-year-old boy who underwent a percutaneous stenting angioplasty for a coarctation of the aorta and developed a cerebral infraction 4 hours after the procedure.